Investigasi Penggunaan Buku Teks Singapura Pada Pembelajaran Matematika - Wiputra Cendana; Kimura Patar Tamba (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Textbooks have a strong influence on curriculum development, learning approaches, activities and even assessments of learning mathematics. The aim of the research is to describe the use of mathematics textbooks based on the Singapore curriculum in mathematics learning. This research is a qualitative research with a case study method. The participant is an elementary school teacher at a school in Tangerang. Data collection was carried out by observation using an observation guide. Data analysis was carried out descriptively using coding. Coding uses Nicol and Crespo's framework regarding the model of using textbooks in mathematics learning, namely adhering, elaboration, and creating and is seen based on the role played by the teacher in the learning process. The results of the study show that the level of teacher use of books is in the adhering category for each teacher's role in using textbooks.